USING THE AUDIO-LINGUAL METHOD IN TEACHING A FOREIGN LANGUAGE - Begimkulova Dilobar; Rustamova Mohinur Xurshid qizi; Aralova Shahrizoda Anvar qizi (Journals Park Publishing, 2024)
This article provides detailed information about another important method of language learning - the audio-lingual method, its origin and history, role in the formation of language skills, cultural and linguistic aims and principles of this method.
Keywords: Audiolingualism, memorisation, Army Method, repetition, dialogue, question-answer approach, achieving clarity, purity, logic of speech, Nosophobia and Glossophobia, grammatical structure, correct pronunciation, vocabulary, Booknomy.